Carbon uptake dynamics of cement-based materials: Linking market structure, material use, and the carbon cycle - Hessam AzariJafari; Ipek Bensu Manav; Motahareh Rahimi; Elizabeth Moore; Bruno Huet; Christophe Levy; Randolph Kirchain (Proceedings of the National Academy of Sciences, 2025)
Cement-based products sequester CO 2 in the atmosphere throughout their life cycle. The extent of sequestration highly depends on the context. We implement a bottom–up model of different cement end-use applications (buildings, pavements, bridges, pipelines, and other infrastructure) in the United States and Mexico to estimate the in-use and end-of-life carbon uptake in cement. We show that carbon uptake in 2024 could sequester approximately 13% of process emissions associated with cement consumption, which is around 6.7 Mt CO 2 . We observe a four-fold variation in the uptake per square area across all the states due to regional differences in the distribution of building types, concrete mix designs, and climates. The building sector uptake is almost twice as large as infrastructure systems. In Mexico, the current stock of cement-based products sequesters around one-quarter of the industry’s annual process emissions, implying the importance of local differences in end-use context, which can dramatically alter the extent of carbon uptake. Where prudent, enhancing carbon uptake in cement-based products is a valuable strategy to move toward carbon neutrality in the construction sector. The findings in this paper provide a fundamental shift in understanding how anthropogenic materials interact with the carbon cycle, which changes how national greenhouse gas inventories are calculated.